Propagation of chaos for the Vlasov-Poisson-Fokker-Planck equation with a polynomial cut-off - Carrillo de la Plata, JA; Choi, YP; Salem, S (World Scientific Publishing, 2018)
We consider a N-particle system interacting through the Newtonian potential with a polynomial cut-off in the presence of noise in velocity. We rigorously prove the propagation of chaos for this interacting stochastic particle system. Taking the cut-off like N−δ with δ<1/d in the force, we provide a quantitative error estimate between the empirical measure associated to that N-particle system and the solutions of the d-dimensional Vlasov–Poisson–Fokker–Planck (VPFP) system. We also study the propagation of chaos for the Vlasov–Fokker–Planck equation with less singular interaction forces than the Newtonian one.